Social Media Marketing, Custumer Enggagement, E-Wom Terhadap Re-Puchase Intention Pada Institute Kopi Café Makassar - Khaeril, Khaeril; Nursyamsi, Nursyamsi; Qadriah, Nurul nurulqadriah13@gmail.com; Nessa, Happy; Faulina, Irviani; Lutfi, Alim (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2024)
This research aims to gain new knowledge and analyze the influence of social media marketing, customer engagement, and electronic word-of-mouth (e-WOM) on re-purchase intention. This type of research uses quantitative research with a survey approach. The population in this research are consumers found in Makassar Café Coffee Institute. The sampling technique uses purposive sampling with a total of 125 respondents. Data collection was carried out by distributing questionnaires directly and distributing Google forms to customers. The analysis technique used is Smart PLS 3.0 Software.Results show that: (1) Social Media Marketing has a negative but not significant influence on Re-Purchase Intention; (2) Customer Engagement has a positive and significant effect on Re-Puchase Intention; (3) e-Wom has a positive but not significant effect on Re-Puchase Intention.